2019
DOI: 10.32637/orli.v49i1.292
|View full text |Cite
|
Sign up to set email alerts
|

ABR profile in children with congenital rubella syndrome at Hasan Sadikin General Hospital

Abstract: Background: Congenital Rubella Syndrome (CRS) refer to a condition of variable birth defects, such as hearing impairment, congenital heart defects, cataract or congenital glaucoma, and others. In Indonesia, the incidence rate of rubella infection in 2015 was 3.2 per 100.000 live birth and increasing to 5.6 per 100.000 live birth in 2017. Rubella vaccination can decrease the incidence of CRS, however it has not been implemented in many developing country. Hearing impairment is the most common clinical manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Thus, immunization is the best and most effective preventive measure to prevent CRS. 3,[13][14][15][16][17][18] In the study, we aimed to evaluate the diagnostic value of group A and group B clinical manifestations compared to rubella serology results in the diagnosis of CRS at Dr. Zainoel Abidin's Regional General Hospital (ZARGH), Banda Aceh. The results of this study are expected to be the basis for early diagnosis of CRS in children aged 0-12 months, especially in health facilities that lack the facilities to perform serological rubella examinations, such as ZARGH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, immunization is the best and most effective preventive measure to prevent CRS. 3,[13][14][15][16][17][18] In the study, we aimed to evaluate the diagnostic value of group A and group B clinical manifestations compared to rubella serology results in the diagnosis of CRS at Dr. Zainoel Abidin's Regional General Hospital (ZARGH), Banda Aceh. The results of this study are expected to be the basis for early diagnosis of CRS in children aged 0-12 months, especially in health facilities that lack the facilities to perform serological rubella examinations, such as ZARGH.…”
Section: Resultsmentioning
confidence: 99%
“…This syndrome can also appear in the form of other congenital disabilities. [1][2][3][4] Congenital rubella syndrome occurred in more than 105,000 infants worldwide in 2010. The World Health Organization (WHO) estimated that 238,000 children are born with CRS before the vaccination's era and that there are 100,000 new cases yearly, especially in developing countries.…”
mentioning
confidence: 99%
“…The same results were also obtained by the study of Gunawan et al 5 which showed that most of the patients with speech delay with ASSR examination had abnormal examination results as profound hearing loss. Another research by Aditomo et al 7 , Wijana et al 8 and Purnami 9 showed that ABR result o n hearing loss cases were mostly profound. Result from those research consecutively were 44.07%, 45%, and 87.27%.…”
Section: Discussionmentioning
confidence: 95%